Efficacy of drip irrigation in controlling heavy-metal accumulation in soil and crop. Issue 3 (10th November 2020) - Singh, Deepak; Patel, Neelam; Patra, Sridhar; Singh, Nisha; Roy, Trisha; Caucci, Serena; Hettiarachchi, Hiroshan
Abstract : This study was aimed at identifying how drip irrigation could be useful in controlling heavy-metal issues, practically and affordably. A vegetable crop (i.e. cauliflower) was the subject of the test. Heavy-metal accumulation in soils and uptake by cauliflower curds were observed for two consecutive years. Municipal wastewater and groundwater were used for irrigation, to make it a comparative study. There were eight treatments: drip irrigation with groundwater through inline (non-pressure-compensating) surface drip (T1 ), inline subsurface drip (T2 ), bioline (pressure-compensating) subsurface drip (T3 ), bioline surface drip (T4 ) and the same drip systems using primarily treated municipal wastewater (T5 to T8 ). The results showed that significantly higher concentrations of heavy metals – namely, copper, iron, manganese and zinc – were recorded in cauliflower curds irrigated with wastewater compared with those irrigated with groundwater. Subsurface placement of pressure-compensating drip laterals was found more effective in reducing the heavy-metal concentrations in both cauliflower and soil profile compared with surface-placed non-pressure-compensating drip laterals. This study suggests that drip irrigation systems could be an effective method to reduce heavy-metal concentration in vegetable crops and soils irrigated with treated municipal wastewater.